Acculturative Stress and Adjustment Experiences of Greek International Students - Poulakis, Mixalis; Dike, Craig A.; Massa, Amber C. (Journal of International Students, 2017)
This study investigated eight Greek international college students’ experiences of acculturation and acculturative stress at a mid-western university in the United States. Semi-structured interviews were conducted with participants and Consensual Qualitative Research methodology was utilized for data analysis to identify contextual themes and domains expressed by participants. Seven domains relevant to extant literature were revealed: presojourn perceptions of the United States; postsojourn perceptions of the United States; acculturative stress problems in the United States; coping strategies for acculturative stress problems; peer and family networks: English language usage and difficulties; and cultural concerns regarding the United States or native country. Implications, areas for future research, and the study’s limitations are also discussed.